Analisis Rasio Profitabilitas Dalam Menilai Kinerja Keuangan Pada PT. Kawasan Industri Makassar (Persero) - Rika Wulandari; Pra Gemini; Meldilianus Meldilianus (Intellektika : Jurnal Ilmiah Mahasiswa, 2023)
This study examines a company's financial records using profitability measures to ensure its financial success. Data for this study were collected from financial records including balance sheets and income statements, and the authors used PT. Makassar Industrial Estate (Persero) as the object of research. Quantitative data is the type of research used in this study. This study examines a company's financial records using profitability measures to ensure its financial success. Data for this study were collected from financial records including balance sheets and income statements, and the authors used PT. Makassar Industrial Estate (Persero) as the object of research. Quantitative data is the type of research used in this study.